Young children's thinking - Dowling, Marion; Sage eBooks (Los Angeles : SAGE, 2013)
Based on the author's current consultancy and training work, this book helps early childhood practitioners and students understand and develop young children's thinking.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Early childhood education; Cognition in children; Electronic books